Efficiency improvement of fluorescent blue device by molecular orientation of blue dopant. Issue 1 (24th April 2014) - Ogiwara, Toshinari; Ito, Hirokatsu; Mizuki, Yumiko; Naraoka, Ryo; Funahashi, Masakazu; Kuma, Hitoshi
Abstract The relationship between molecular shape of fluorescent blue dopants (BDs) and degree of molecular orientation was studied. BDs with larger ovality showed higher degree of orientation and higher external quantum efficiency (EQE) over 10% in a fluorescent blue device. Impedance spectroscopy, transient electroluminescence spectroscopy, and optical simulation results highly indicated that such high EQE was originated mainly from the optical effect of horizontal‐aligned BDs. Furthermore, a higher EQE of 11.5% at a current density of 10 mA/cm2 was successfully achieved by modifying molecular structure of BD.